Body, space and community. Notes for an anthropological understanding of the quarantine experience - Palacios Cruz, Víctor Hugo (2022)
The recent experience of quarantine, due to a still ongoing pandemic, which has deprived us for months of a common space and the coincidence with the other. This deprivation has been necessary by sanitary reasons. Nevertheless it has been serious from the point of view of an idea of the human which is not an accidental being but also it is constitutively corporeal and social. Indeed, the representation of the body and the social dimensión as inherent variables to the person allow us to judge better the consequences of the damage which face the share areas, especially Within the cities, in Latin America and even more in Peru. The public space is not an opposed area to the self, but it even explains its identity and freedom. The physical state of the inhabited place adjusts the way in which humans live. The walk of a city is not indifferent to whom we are, which is only fully within a life in common, which cannot be abandoned because of the “new normalcy”, it means, in a time of social fear and dominant protagonism of virtuality.